2020
DOI: 10.3390/md18100487
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Acne Effects of Cembrene Diterpenoids from the Cultured Soft Coral Sinularia flexibilis

Abstract: Acne is a skin disease common in adolescents and increasingly common in the adult population. The major pathologic events of acne vulgaris include increased sebum production, retention hyperkeratosis, carrying commensal skin microbiota, and inflammation. In recent years, more than 10,000 compounds have been isolated and identified from marine organisms. The aim of this study was to discover the potential anti-acne activity of fraction 9 + 10 (SF-E) of Sinularia flexibilis extract and six cembrene diterpenoids.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…The strong antimicrobial activity of these essential oils might be due to synergistic effects of chemical constituent (both lipophilic and hydrophilic) present in the EOs, like β-caryophyllene [ 36 , 37 ], carvacrol [ 49 ], carvone [ 50 ], cembrene [ 51 ], eugenol [ 52 , 53 ], γ-terpinene, 1,8-cineole, α-terpinene [ 54 ], α-terpineol [ 55 ], α-Himachalene, α-Humulene [ 37 ], and (E)-Anethol [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The strong antimicrobial activity of these essential oils might be due to synergistic effects of chemical constituent (both lipophilic and hydrophilic) present in the EOs, like β-caryophyllene [ 36 , 37 ], carvacrol [ 49 ], carvone [ 50 ], cembrene [ 51 ], eugenol [ 52 , 53 ], γ-terpinene, 1,8-cineole, α-terpinene [ 54 ], α-terpineol [ 55 ], α-Himachalene, α-Humulene [ 37 ], and (E)-Anethol [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…The essential oils were more effective against the Gram-positive strain than the Gram negative; it might be due to the presence of more lipophilic constituents in the essential oils. The strong antimicrobial activity of these essential oils might be due to synergistic effects of chemical constituent (both lipophilic and hydrophilic) present in the EOs, like β-caryophyllene [36,37], carvacrol [49], carvone [50], cembrene [51], eugenol [52,53], γterpinene, 1,8-cineole, α-terpinene [54], α-terpineol [55], α-Himachalene, α-Humulene [37], and (E)-Anethol [53].…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…C. acnes can induce the inflammatory response of macrophages or monocytes, leading to the release of proinflammatory cytokines. According to previous studies, proinflammatory cytokines can promote the emergence of skin adhesion molecules and hypersensitivity response with the production of protease, hyaluronidase, and chemotactic factors [2].…”
Section: Anti-inflammatory Activitiesmentioning
confidence: 97%
“…This condition decides about 85% of people, especially prevalent among young adolescents [1]. Acne is associated with the increase of sebum production by overactive oil glands, the hyperkeratinization by blocking skin pores, the successive release of skin inflammatory mediators and the bacterial colonization in the follicles leading to the carrying of commensal skin microorganisms [2]. Three main Gram-positive bacteria, Cutibacterium acnes (formerly Propionibacterium acnes), Staphylococcus epidermidis and Staphylococcus aureus, are involved in the bacterial colonization of the follicle.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that Staphylococcus epidermidis dysbiosis can cause infection of hair follicle sebaceous glands, which can lead to acne [3]. In addition, abnormal proliferation of keratinocytes can block the hair follicle sebaceous glands and result in the formation of acne [4]. Therefore, most drugs to treat acne (salicylic acid, antibiotics, and anti-in ammatory drugs) are targeted to the above two important factors, S. epidermidis infection and abnormal proliferation of keratinocytes [3]; however, these drugs can cause a variety of side effects and long-term use of antibiotics may result in antibiotic resistance in acne-causing bacteria [5].…”
Section: Introductionmentioning
confidence: 99%